Factors that affecting customer's purchase intention towards fast food in Kota Kinabalu / Haslinda Hasan - Hasan, Haslinda (2016)
Fast food business nowadays rises up among the business entrepreneur as their chosen medium to engage with customer to match consumer’s daily lifestyle of the current development. Malaysia is one of the countries which are not excluding from this current trend of development. It is therefore essential for companies to continuously develop their fast food business and attract new customers. To do so, entrepreneur need to develop the understanding on the current customer's needs and preferences that might capture their attention towards purchasing foods decision.